Pemeliharaan Larva Kerapu Bebek (Cromileptes altivelis) dengan Konsentrasi Pewarna Hijau Media Air yang Berbeda - Suko Ismi; Wardoyo Wardoyo; Ketut Setyawati; Tridjoko Tridjoko; Jhon H. Hutepea (Universitas Gadjah Mada, 2006)
The purpose of this research was to find the optimum color concentration of water for larval rearing of humbpback grouper (Cromileptes altivelis). The experiment conducted using 12 polycarbonat tanks with volume of 200 l. Initial density of larvae was 10 ind/l. Food grade coloring agent was used to result a green color water solution. Four different water color concentration were tested as treatments i.e.: A 10 ppm; B 20 ppm ; C 30 ppm and D 40 ppm with three replications. The experiment was conducted for 30 days. The result showed that the highest survival rate was exhibited by C treatment (30 ppm) (P<0.05), the B (20 ppm) and D (40 ppm) treatments were significantly different (P<0.05) compare to A (10 ppm.) The survival rates of larvae at the end of experiment were A (8.2%); B (25.6%); C (40.4%) and D (29.3%).